ANORECTAL PATHOLOGIES IN THE COURSE OF ACUTE LEUKAEMIAS: PREDICTIVE PARAMETERS - Fatma Yılmaz; Bugra Saglam; Ufuk Gorduk; Ugur Kalan; Hacer Berna Afacan Öztürk; Ahmet Kursad Gunes; Murat Albayrak (Mediterranean Journal of Hematology and Infectious Diseases)
Introduction. Patients with leukaemia are exposed to infections as long as they are neutropenic. During this period, anorectal pathologies are among the common foci of infection with high mortality. We aimed in this study to investigate the factors that may have a predictive effect for early diagnosis and rapid intervention in perianal complications occurring in neutropenic patients diagnosed with leukaemia.